Internalisasi Nilai Islam di era Post-truth: Instagram dr@zaidulakbar sebagai Media Literasi Informasi Kesehatan - Ditha Prasanti (Institut Agama Islam Negeri Kendari, 2020)
Author explains Instagram account about Islamic and health information. In the current post-truth era, when a variety of health information that is spread is not necessarily true, it can be justified or assumed to be true, the account of dr@zaidulakbar is present to counter the issue of health hoaxes. The author wants to know the process of internalizing Islamic values in the post-truth era through the account of dr@zaidulakbar as a media for literacy in health information. How not, as a doctor, his name became a credible source by carrying the mission of his mission in spreading health information to the public. The Instagram account has 2.1 million followers with a tagline that